Beyond Technical Skills: The Full Mediation of Self-Efficacy in the Relationship between Employability Skills and Work Readiness - Arlita Wulandari; Bungaran Saing; Dian Sudiantini (Journal Of Economic Cluster, 2026)
This study aims to analyze the effect of employability skills on student work readiness with self-efficacy as a mediating variable. The subjects of this study were undergraduate (S1) students of the Management Study Program, Class of 2022, at Universitas Bhayangkara Jakarta Raya. The study used a quantitative approach with an explanatory design. The population consisted of 349 students, with an explicit sample size of N = 78 respondents determined using the Slovin formula and selected via a simple random sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using Path Analysis with Partial Least Squares (PLS) Structural Equation Modeling (SEM) using SmartPLS 3.0 software. The results showed that employability skills did not have a significant direct effect on work readiness (coefficient 0.053, p-value 0.763). However, employability skills had a positive and significant effect on self-efficacy (coefficient 0.760, p-value 0.000), and self-efficacy had a positive and significant effect on work readiness (coefficient 0.685, p-value 0.000). Furthermore, self-efficacy positively and significantly mediated the effect of employability skills on work readiness (coefficient 0.521, p-value 0.000). This finding suggests that improving student work readiness is more effectively achieved through strengthening self-efficacy as a psychological mechanism that bridges employability skills with work readiness.